Korelasi Antara Cara Orangtua Mendidik dengan Prestasi Belajar : (Studi Kasus: SMA Swasta Nurhasanah Medan) - Dewi Risanti (Institute of Computer Science (IOCS), 2021)
The ways, forms and content of education provided by parents to children will affect the growth and development and learning achievement of children, therefore parents should not be separated in fostering and developing all the potential of children in order to improve their children's learning achievement in the family environment by trying to create a good atmosphere and learning environment, which of course can affect learning achievement. In this study, the authors determined the population of students of class XII IPA and IPS Of Nurhasanah Medan Private High School who lived with parents as many as 38 people, the sample was determined as many as 30 people taken through random sampling techniques. To collect data, closed questionnaires are used, to obtain data on how parents educate and documentary studies to obtain student learning achievement. Respondents' answers are given a value by giving a value weight for option a given a value of 4, for option b is given a value of 3, and for option c is given a value of 2, and for option d is given a value of 1. To find a correlation between the way parents educate and learning achievement is used pearson product moment formula as follows : To test a hypothesis with a significant level of 5% or by using a belief level of 95% used a table r (correlation table) with a sample number of 30 people which is 0.361. Thus the result of the calculation obtained the value r = -0.24 cannot prove the hypothesis. The results of the conclusions in the study stated a negative relationship between the way parents educate and student learning achievement. So the author can conclude that the way parents educate good influences low on student learning achievement at Nurhasanah Medan Private High School.